Role of Civil Society Organizations in Promoting Transparency and Accountability in Kabale Municipality: A Case Study of Kick Corruption out of Uganda (Kick-U) Kabale Branch. - Namanya, Benson Benon (Kabale University, 2025)
This study explored the challenges and opportunities for transparency and accountability in Kabale Municipality, focusing on factors influencing the effectiveness of these mechanisms. The specific objectives were to: (i) examine the relationship between transparency and corruption in the municipality, (ii) investigate the impact of accountability on citizen participation in decision-making, and (iii) assess the effectiveness of the municipal council's transparency and accountability mechanisms in reducing corruption and enhancing citizen engagement. The findings aim to provide insights into improving governance and fostering trust between the municipal council and its stakeholders.